The Routledge handbook of contemporary philosophy of religion - Oppy, Graham Robert (London Routledge, 2015)
Philosophy of religion has experienced a renaissance in recent times, paralleling the resurgence in public debate about the place and value of religion in contemporary Western societies. The Routledge Handbook of Contemporary Philosophy of Religion is an outstanding reference source to the key topics, problems and debates in this exciting subject -- provided by Publisher.
Theoretical orientations -- Conceptions of divinity -- Epistemology of religious belief -- Metaphysics and religious language -- Religion and politics -- Religion and ethics -- Religion and scientific scrutiny.
Includes bibliographical references (pages 434-465) and index.
Keywords: Religion -- Philosophy